THE ROLE OF ACCOUNTANTS IN IMPLEMENTATION CORPORATE SOCIAL RESPONSIBILITY AT HOSPITAL Dr. H. MOH. ANWAR SUMENEP DISTRICT - Syahril Syahril; Isnani Yuli Andini (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2017)
Internal accountants has critical leverage to encourage hospitals to be involved in activities such as social or corporate social responsibility.This study aims to examines the role of internal accountants in the implementating of corporate social responsibility at RSUD Moh. Anwar Sumenep District. Research uses descriptive (qualitative) approach to interpret and describe data that obtained from observation, interview and documentation. This research concludes that RSUD Moh. Anwar Sumenep District does not have a clear standard about corporate social responsibility. Its only depends on the willingness of the organization, not an obligation to disclose in hospital financial statements. Internal accountant who is in charge of performing systematic and objective analysis and assessment on the operation and control of company's activities is needed to encourage companies to carry out social responsibility. Researcher suggest that governments needs to increasing their concern toward this issues whether in the form of programs, policies, regulations or awards of the social environment.Keywords: Internal Accountant, Corporate Social Responsibility, Hospital